AGE, GROWTH AND ARCHITECTURE OF THE HISTORIC BIG TREE AT VICTORIA FALLS, ZIMBABWE ASSESSED BY RADIOCARBON DATING - Patrut, Adrian; Patrut, Roxana T.; Rakosy, Laszlo; RATIU, ILEANA ANDREEA; Lowy, Daniel A.; von Reden, Karl F. (Dendrochronologia, 2021)
The article discloses the AMS (accelerator mass spectrometry) radiocarbon dating results of the historic Big Tree at Victoria Falls, Zimbabwe. The research aimed to determine the age, growth and architecture of this renowned African baobab. The superlative baobab is composed of five main stems, three young stems and one false stem. It exhibits an open ring-shaped structure, an architecture that allows baobabs to reach large sizes and old ages. Several wood samples extracted from four stems were dated by radiocarbon. The oldest sample had a radiocarbon date of 978 ± 14 BP, corresponding to a calibrated age of 955 ± 20 calendar years. By this value, the Big Tree at Victoria Falls is 1150 ± 50 years old. We found that the eight common stems belong to three generations, which are 1000-1100, 600-700 and 200-250 years old, respectively. The false stem is 550 years old. The stems belonging to the oldest generation stopped growing over 100 years ago.
Keywords: Adansonia digitata; Age determination; AMS radiocarbon dating; growth stop; multiple stems; tropical trees